2005
DOI: 10.1111/j.1365-2605.2005.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm concentration in Latvian military conscripts as compared with other countries in the Nordic–Baltic area

Abstract: Recent studies of semen quality in men from the general population gave rise to the hypothesis of an East-West gradient in semen quality in the Nordic-Baltic area, with the highest sperm counts in Estonia, Lithuania and Finland, and the lowest in Denmark (30% difference in mean concentration). Genetic, lifestyle-related and environmental factors - alone or in combination - were suggested to be responsible for these differences. The aim of this study was to assess sperm concentration in men from the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
4
26
1
Order By: Relevance
“…The positive significant correlation found between testicular cancer and cryptorchidism among 'high-quality matching coverage' registries outside Europe is consistent with studies showing a markedly higher Jørgensen et al, 2002;Punab et al, 2002;Richthoff et al, 2002;Tsarev et al, 2005;Paasch et al, 2008;Fernandez et al, 2012. risk of testicular cancer is in men with a history of cryptorchidism (Swerdlow et al, 1997;Schnack et al, 2010). Orchidopexy (the surgical displacement of the testes to the scrotum of cryptorchid boys) was suggested to reduce the risk of testicular cancer in one study (Pettersson et al, 2007) but this was not confirmed in another larger study (Myrup et al, 2007).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The positive significant correlation found between testicular cancer and cryptorchidism among 'high-quality matching coverage' registries outside Europe is consistent with studies showing a markedly higher Jørgensen et al, 2002;Punab et al, 2002;Richthoff et al, 2002;Tsarev et al, 2005;Paasch et al, 2008;Fernandez et al, 2012. risk of testicular cancer is in men with a history of cryptorchidism (Swerdlow et al, 1997;Schnack et al, 2010). Orchidopexy (the surgical displacement of the testes to the scrotum of cryptorchid boys) was suggested to reduce the risk of testicular cancer in one study (Pettersson et al, 2007) but this was not confirmed in another larger study (Myrup et al, 2007).…”
Section: Discussionsupporting
confidence: 62%
“…We did not use data from studies performed among fertile men (partners of pregnant women) as they do not reflect the situation Geographical analysis of male reproductive disorders in general population: infertile men and subfertile men are underrepresented or not included in those studies and thus the results of semen characteristics are inevitably higher. General population data were available for nine European cities: Turku, Finland; Oslo, Norway; Copenhagen, Denmark; Tartu, Estonia (Jørgensen et al, 2002), Malmö , Sweden (Richthoff et al, 2002); Riga, Latvia (Tsarev et al, 2005); Kaunas, Lithuania ; Almeria, Spain (Fernandez et al, 2012) and Leipzig, Germany (Paasch et al, 2008).…”
Section: Sperm Quality Datamentioning
confidence: 99%
“…There are two publications of investigations performed in 1996 -1997 describing the reproductive health of young Lithuanian men separately from Estonians (8), and Latvian men (9). Even from this study of 226 young Lithuanians, we noticed some differences of reproductive parameters between Lithuania and Estonia, but we failed to explain these differences.…”
Section: Institute Of Endocrinology Lithuanian University Of Health contrasting
confidence: 59%
“…Possible ethnic differences in sperm concentration were observed in Latvia (9). Only sperm analysis was published, without hormone investigation.…”
Section: Institute Of Endocrinology Lithuanian University Of Health mentioning
confidence: 97%
“…The Latvian patient group consisted of 92 men with oligoasthenoteratozoospermia, which was defined as low sperm motility (progressive sperm motility <20%), low sperm concentration (<15 million/mL), and a low percentage of sperm with normal morphology (<4%). One control group consisted of 187 young men (age, 18-25 years) from the Latvian general population with normal semen quality and unknown fertility, for whom the collection criteria were described previously [7] . The other control group consisted of 200 men, randomly selected from the Latvian National Genome Database known to have 5 children; hence, these men were proven fertile, but had unknown semen quality.…”
Section: Patientsmentioning
confidence: 99%